2018
DOI: 10.7554/elife.39249
|View full text |Cite
|
Sign up to set email alerts
|

Humidity response depends on the small soluble protein Obp59a in Drosophila

Abstract: Hygrosensation is an essential sensory modality that is used to find sources of moisture. Hygroreception allows animals to avoid desiccation, an existential threat that is increasing with climate change. Humidity response, however, remains poorly understood. Here we find that humidity-detecting sensilla in the Drosophila antenna express and rely on a small protein, Obp59a. Mutants lacking this protein are defective in three hygrosensory behaviors, one operating over seconds, one over minutes, and one over hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…One functional study in D. melanogaster found robust OSN responses even after the sole OBP from the corresponding sensillum had been knocked-out (Larter et al 2016). Another study identified a role for an OBP in humidity sensing (Sun et al 2018). It, therefore, remains to be seen how OBPs or other accessory proteins might contribute to the evolution of olfactory behavior (but see Matsuo et al 2007 for a clear example of an OBP driving the evolution of taste responses).…”
Section: Changes In Osn Tuning Via Accessory Protein Evolutionmentioning
confidence: 99%
“…One functional study in D. melanogaster found robust OSN responses even after the sole OBP from the corresponding sensillum had been knocked-out (Larter et al 2016). Another study identified a role for an OBP in humidity sensing (Sun et al 2018). It, therefore, remains to be seen how OBPs or other accessory proteins might contribute to the evolution of olfactory behavior (but see Matsuo et al 2007 for a clear example of an OBP driving the evolution of taste responses).…”
Section: Changes In Osn Tuning Via Accessory Protein Evolutionmentioning
confidence: 99%
“…Many of the most highly expressed genes in the antenna are those encoding Odorant Binding Proteins (OBPs), which are transcribed in nonneuronal cells, often at >10-fold higher levels than olfactory receptor genes, as determined by bulk RNA-seq 31,34 . Two of these, Obp59a and Obp84a are present in sensilla housing Ir neurons 37,38 , but neither of these genes display significant OSs in any neuron population ( Figure 1G). Similarly, markers for other support cell types, such as nompA (thecogen cell) 37,39 , and the glial marker repo are not significantly occupied ( Figure 1G).…”
Section: Results Targeted Damid Of Osn Populationsmentioning
confidence: 99%
“…Nevertheless, there are some OBPs that are conserved and have orthology relationships with counterparts from other Dipterans. For example, HillOBP1 and 2 are homolog to OBP83b found in B. dorsalis, HillOBP11 is a homolog to Lush found in D. melanogaster, and HillOBP9 is a homolog to DmelOBP59a found in D. melanogaster (Pikielny et al, 1994;Galindo and Smith, 2001;Wu et al, 2015;Sun et al, 2018). Both OBP83b and Lush have been reported to play roles in sensing semiochemical attractants and the pheromone 11-cis vaccenyl acetate (Xu et al, 2005;Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%